Optimal harvesting of the nonlinear population dynamics - Anita, Sebastian (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with an optimal harvesting problem for a nonlinear age-dependent population dynamics. The existence and uniqueness of a positive solution for the model considered is demonstrated. The existence of an optimal harvesting effort and the convergence of a certain fractional step scheme are investigated. Necessary optimality conditions for some approximating problems are established.
Keywords: population dynamics; Carathéodory solution; optimal harvesting; fractional step scheme; necessary optimality conditions